Preparation of2 - thio ether - 1, 3, 4- oxadiuzole derivatives used asantibacterial and antifungus agents - M-Daher Al-joubory, Abed-; S- Hamad, Ayad - (Tikrit Journal of Pharmaceutical Sciences, 2023)
bs tract Isonicotinic acid, o-hydroxy benzoic acid, p-chlorobenzoic acid p-nitro benmteacid and 0-acetyl benzoic acid, have ben csterificated with absolute ethanol wing Fisher method to prepare compounds [I-5J. -Most compounds %vac converted to acid hydra idef; [6-10] by the reaction with hydrazine hydrate. The avid hydrazides were allowed to react with carbon disulfide (CS2) in the presence of potassium hydroxide and ethanol to pmduce 2-substituted 1, 3, 4- oxadia7nic -5-thiol 111-15]. Thio ether derivatives as two groups (16-20) and (21-25) respectively have been prepared by the reaction between compounds 111-15] and alkyl or aryl halide, (p-bromn bcnzyl bromide and 2.4- dinitrochlurubenzene) respectively. The prepared compounds Were identified by FI_LR melting point and I WAS used to support the structure of the compounds 2-(4-chloropheny1)-5-(2,4- dini trophcny I thio)- 1 ,4-oxad iazo le and 2-(2,4-d initropheny I dtio)-3-(4-nitrophenyl)- I ,3,4- oxadiszole which can be uazd as anti bactaial and anti fungus agents